Regeneration of five commercially-valuable tree species after experimental logging in an Amazonian forest - Albertina Pimentel Lima; Odilon Pimentel de Lima; William Ernest Magnusson; Niro Higuchi; Francisco Quintiliano Reis (Revista Árvore, 2002)
This study investigated the regeneration variation of five commercially valuable tree species in relation to different intensities of felling in fourteen 4-ha plots in an area under experimental forest management. This experiment was carried out in a typical Amazonian tropical forest sample on "terra-firme," in Manaus (AM). Plots were logged 7 and 8 years (1987 and 1988), or 3 years (1993) before the study. All trees with height greater than 2 m, and diameter at breast height (DBH) smaller than 10 cm were measured. Only Aniba hostmanniana, Ocotea aciphylla, Licaria pachycarpa, Eschweilera coriacea and Goupia glabra were sufficiently common for individual analyses. These species have high timber values in the local market. Eight years after logging, the species responded differently to logging intensities. The numbers of individuals of Goupia glabra and Aniba hostmanniana were positively related to the intensity of logging, while Ocotea aciphylla, Licaria pachycarpa, and Eschweilera coriacea showed no statistically significant response. In the most recently (1993) logged areas, Goupia glabra and Aniba hostmanniana had higher numbers of individuals than the control plots.